Impact of divalent cations on lysozyme-induced solubilisation of waste-activated sludge: Perspectives of extracellular polymeric substances and surface electronegativity. (September 2022) - He, Junguo; Zhang, Pengfei; Zou, Xiang; Zhong, Yijie; Pan, Xinlei; Pang, Heliang; Zhang, Jie; Cui, Xinxin; Wu, Xuewei; Li, Biqing; Tang, Xia; Xiao, Xiannian
Abstract: Lysozyme hydrolysis can accelerate waste-activated sludge (WAS) solubilisation, which can significantly shorten the process and promote the efficiency of anaerobic digestion. This study investigated the impact of divalent cations on lysozyme-induced solubilisation of WAS. The performance of lysozyme pretreatment was dramatically inhibited by Mg 2+ and Ca 2+ . Compared to the control group, the amount of net SCOD, protein, and polysaccharides released to the supernatant were reduced by 36.6%, 44.7%, and 35.8%, respectively, in the presence of divalent cations. The extracellular polymeric substance (EPS) matrix became tightly bound, resulting in fewer proteins and polysaccharides being extracted from loosely-bound EPS (LB-EPS) with divalent cations, which was detrimental to the solubilisation of WAS. Divalent cations decreased the surface electronegativity of sludge particles and prolonged the adsorption of lysozymes by sludge flocs. More than 16.6% of total lysozymes remained in the liquid phase of WAS after 240 min Mg 2+ and Ca 2+ strengthened the binding among proteins and polysaccharides and promoted the intermolecular cross-linking of polysaccharides. The EPS matrix formed a dense spatial reticular structure that blocked the transfer of lysozymes from the EPS matrix to the pellet. As a result, the lysozymes accumulated in LB-EPS rather than hydrolysing the microorganism's cell wall. This study provides a new perspective on the restriction of WAS pretreatment with lysozymes and optimises the method of lysozyme-induced solubilisation of WAS. Graphical abstract: Image 1 Highlights: Mg 2+ and Ca 2+ inhibited the performance of lysozyme-induced solubilisation of WAS. Surface electronegativity reduction caused lysozymes trapped in the liquid phase. Lysozymes accumulated in the outer layer of sludge flocs with Mg 2+ and Ca 2+ . Mg 2+ and Ca 2+ enhanced the intermolecular cross-linking of polysaccharides. Dense spatial reticular structure was formed in extracellular polymeric substances.